First-principles study of the structural, optoelectronic and thermophysical properties of the π-SnSe for thermoelectric applications - Sattar, Muhammad Atif; Al Bouzieh, Najwa; Benkraouda, Maamar; Amrane, Noureddine (Beilstein Journal of Nanotechnology, 2021)
Tin selenide (SnSe) has thermoelectric (TE) and photovoltaic (PV) applications due to its exceptional advantages, such as the remarkable figure of merit (ZT ≈ 2.6 at 923 K) and excellent optoelectronic properties. In addition, SnSe is nontoxic, inexpensive, and relatively abundant. These aspects make SnSe of great practical importance for the next generation of thermoelectric devices. Here, we report structural, optoelectronic, thermodynamic, and thermoelectric properties of the recently experimentally identified binary phase of tin monoselenide (π-SnSe) by using the density functional theory (DFT). Our DFT calculations reveal that π-SnSe features an optical bandgap of 1.41 eV and has an exceptionally large lattice constant (12.2 Å, P213). We report several thermodynamic, optical, and thermoelectric properties of this π-SnSe phase for the first time. Our finding shows that the π-SnSe alloy is exceptionally promising for the next generation of photovoltaic and thermoelectric devices at room and high temperatures.
Keywords: density functional theory (DFT); electronic properties; lattice thermal conductivity; optical properties; thermodynamic properties; thermoelectric properties; tin selenide (SnSe)